Relationships between Illness Perception and Needs Assessment in Patients with Oncohematological Diseases - Račkauskaitė, Emilija; Brasaitė-Abromė, Indrė (Slauga. Mokslas ir praktika, 2025)
Patients with oncohematological diseases often have problems with their physical and psychological health. Assessment of illness perception and needs is important in nursing because they are interconnected and determine the effectiveness of treatment, patient well-being and satisfaction. Nurses and other professionals have an important role to play in helping patients understand their illness and related issues, and helping them meet their needs. In order to achieve a patient’s comprehensive health, it is of importance that nurses would meet not only their most necessary physiological needs, but also their psychosocial needs. The purpose of the study is to investigate the perception of the illness and the needs of patients with oncohematological diseases. A quantitative study was carried out. The instrument used is a questionnaire. The questionnaire consisted of sociodemographic questions created by the authors of the study, the Short Illness Perception Scale (BIPQ), and the Needs Evaluation Questionnaire (NEQ). The study was conducted in June–September 2024. The sample consisted of 266 respondents. Descriptive data analysis was performed by using the SPSS program. The results of the study showed that patients are very concerned about their disease and feel that the disease affects their lives strongly, they believe that treatment can help them, the disease will not last a long time, they feel that they cannot control their disease, but they appreciate that they understand their disease well. The patients who participated in the study expressed their most urgent needs as those related to relationships, the communication process, and to obtaining information about future forecasts. When evaluating the correlations between the perception of the disease and the needs, it was found that, as the perception of the threat of the disease increases, the sum of the number of individual types of needs increases.
Keywords: oncohematological diseases; illness perception; patient needs; role of nurses; connections